Pembaharuan Strategi dan Metode Pembelajaran pada Jurusan MIPA Di MA Abu Amr - Mustaidah, Lailatul; Maisaroh, Ighfirli; Karimah, Luklu'ul; Ariyanti, Lisa (FKIP Universitas Wisnuwardhana, 2023)
In the learning process, teachers play an important role in implementing effective and efficient learning. Teachers need several strategies and methods used in order to improve student learning outcomes. This study aims to determine the effectiveness of strategies and methods applied in class X MA Abu Amr. The research method used is the survey method, through interviews and distributing questionnaires in the form of paper questions to 24 students. Then the data collection techniques in this study include observation, interviews, and documentation. Based on the results of the study, it can be concluded that the methods and strategies by MA Abu Amr in class X are effective, but due to minimal facilities, students are less satisfied in the learning process and learning seems monotonous. The lack of facilities at MA Abu Amr is due to the majors system carried out in class XI in accordance with the independent curriculum, the reason the school has not completed the facilities is because it is feared that there will be a lack of interest in new students in the MIPA department. However, from the results of the research, it was found that there was a fairly high interest from MA Abu Amr students in the MIPA major.